PRECURSORY SEISMICITY CHANGES ASSOCIATED WITH THE NEMURO PENINSULA EARTHQUAKE, JANUARY 28, 2000 - Huang Q.; Sobolev G.A. (My University, 2002)
We investigated the characteristics of the precursory seismicity changes associated with the M=6.8 Nemuro Peninsula earthquake, January 28, 2000 by applying the RTL (Region–Time–Length) algorithm to the earthquake catalogue of the Japan Meteorological Agency (JMA). The RTL parameters at the epicentre indicated that a seismic quiescence started in 1995 and reached its minimum during October 1996. An activation stage with a duration of about eight months followed. Our detailed investigations indicated that the RTL anomaly around 1996 was not an artificial effect due to the changes of the model parameters, the upgrade of the JMA seismic network or the process of aftershock elimination. The spatial distribution of quiescence in 1996 revealed a significant anomaly in a broad region around the epicentre of the Nemuro Peninsula earthquake. Following the quiescence stage, an activation zone, which was on the order of the rupture length of this earthquake, was obtained around the epicentre during October 1996–July 1997. The consistency of the rupture region and the anomalous activation zone that appeared after the seismic quiescence stage may provide useful information for determining the future risk zones. This study may strengthen the understanding of the seismogenic process of strong earthquakes.